A cost-effective o-toulidine-based Schiff base as an efficient sorbent for metal ion uptake from aqueous and soil samples: Synthesis, antimicrobial, and acute toxicity analyses - Khan, Noureen; Jamil, Nelofer; Jabeen, Rukhsana; Akhtar, Malik Muhammad; Ali, Hussain; Mehmood, Rashad; Orfali, Raha; Perveen, Shagufta; Peng, Jiangnan; Al-Taweel, Areej M. (Frontiers in Environmental Science, 2023)
Heavy metals create serious health problems, so the practical implementation and development of low-cost sorbent materials to remove heavy metals from the ecosystem is a worldwide issue. The purpose of this study is to find a low-cost ligand that has the potential to adsorb heavy metals from aqueous and soil samples and also has biological potential. For this, a Schiff base, dimeric o-toluidine (SBL), has been synthesized through condensation, characterized by spectroscopic analysis, and had its biological activities measured. We also studied its adsorption efficiency through a batch technique to remove Zn(II), Co(II), and Cu(II) from aqueous and soil samples under different conditions such as metal ion concentration, pH, contact time, and SBL concentration. The adsorption potential of SBL was analyzed by the Langmuir and Freundlich adsorption isotherms. The values of correlation coefficients revealed that the Freundlich isotherm elucidated results that were more appropriable than the Langmuir model. Adsorption equilibrium was established in 90 min for aqueous samples and in 1,440 min for soil samples. For the maximum adsorption of all metals, the optimum pH was 8, and it showed a capacity to remove 77 to 95 percent of metals from the samples. The maximum adsorption capacity (qmax) of SBL were 75.75, 62.50, and 9.17 mg g-1 in the case of Cu(II), Zn(II), and Co(II) ions, respectively, from aqueous samples and 10.95, 64.10, and 88.49 mg g-1 in the case of Zn(II), Cu (II), and Co(II), respectively, from soil samples. The effectiveness of SBL in the sorption of the selected metals was found to be Cu+2 > Zn+2 > Co+2 for aqueous samples and Co+2 > Cu+2 > Zn+2 for soil samples. The antimicrobial activity of SBL was also investigated. The results revealed that SBL showed moderate inhibitory activity against Staphylococcus dysentria, C. albican, and Aspergillus niger, whereas it exhibited weak activity against S. aureus, P. aureginosa, K. pneumoniae, P. vulgaris, and E.coli when compared to Fluconazole and Ciprofloxacin as the standard. Acute toxicity of the synthesized compound was measured through its daily oral administration with various doses ranging from 0.1 to 1,000 mg/kg of the mice’s body weights. Even at the dose of 1,000 mg/kg, the SBL showed no mortality or any type of general behavioral change in the treated mice. Based on preparation cost, metal removal capacity, toxicity, and antimicrobial activities, SBL is an excellent sorbent and should be studied at pilot scale levels.